Protein Tyrosine Phosphatase SHP-1 Fails to Associate with Cytoskeleton but is Normally Phosphorylated upon Thrombin Stimulation of Thrombasthenic Platelets - Li, Ruo Ya; Gaits, Frédérique; Ragab-Thomas, Jeannie M F; Maclouf, Jacques; Caen, Jacques P; Lévy-Toledano, Sylviane; Chap, Hugues (Thrombosis and Haemostasis, 1997)
SHP-1 is a cytoplasmic protein tyrosine phosphatase predominantly expressed in hematopoietic cells. Upon thrombin stimulation of human platelets, SHP-1 is rapidly phosphorylated on both serine and tyrosine residues, and becomes associated with the cytoskeleton, where it could participate in the formation of multiprotein signalling complexes. In order to discriminate between signalling events occurring downstream of G-protein-coupled thrombin receptor and those subsequent to integrin αIIbβ3engagement, SHP-1 behaviour was examined in platelets from two patients lacking integrin αIIbβ3 (Glanzmann’s thrombasthenia). Upon thrombin stimulation, phosphorylation of SHP-1 occurred normally in thrombasthenic platelets, whereas association with the cytoskeleton was abolished. Moreover, inhibition of normal platelet aggregation with the tetrapeptide arg-gly-asp-ser (RGDS), which impairs fibrinogen binding to integrin aIIb(33, did not alter significantly SHP-1 phosphorylation. It is concluded that SHP-1 phosphorylation is not a consequence of integrin signalling but might rather occur downstream of thrombin receptor and heterotrimeric G-proteins.